2019
DOI: 10.1002/ima.22311
|View full text |Cite
|
Sign up to set email alerts
|

Rectal cancer: Toward fully automatic discrimination of T2 and T3 rectal cancers using deep convolutional neural network

Abstract: Preoperative chemoradiotherapy is known to reduce the local recurrence of locally advanced rectal cancer. However, the careful use of preoperative chemoradiotherapy is essential, because unnecessary over‐treatment can result in unintended complications. Therefore, a diagnostic system for distinguishing between T2 and T3 rectal cancers should be developed. According to the diagnostic criteria for rectal cancer, radiologists first identify the locations and the shapes of both the tumor and the rectum from a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Other studies of automated T staging in other cancers, such as non‐small‐cell lung cancer and rectal cancer, have been reported, and the results are satisfactory . The deep‐learning system developed by Choi et al for staging liver fibrosis outperformed radiologists .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies of automated T staging in other cancers, such as non‐small‐cell lung cancer and rectal cancer, have been reported, and the results are satisfactory . The deep‐learning system developed by Choi et al for staging liver fibrosis outperformed radiologists .…”
Section: Discussionmentioning
confidence: 95%
“…Newly emerged deep‐learning‐based automatic methods have provided us with an opportunity for automatic staging . Many studies have reported the successful application of deep learning for some similar automated tasks, such as disease classification, pathological tumor classification, automated rectal cancer staging, and automated non‐small‐cell lung cancer staging …”
mentioning
confidence: 99%
“…Some recent studies have tried to estimate rectal cancer-related parameters on preoperative MR images using AI, and have shown that the accuracy was acceptable [22,[26][27][28]. However, these studies had several limitations: tumor tissue was not visualized on the MR image, the relationship of the tumor with the mesorectal fascia was difficult to assess, the results were not based on high-resolution MRI, or the ground-truth labels were not based on pathological assessment, the last issue being the one we consider to be most critical.…”
Section: Discussionmentioning
confidence: 99%
“…The Faster R-CNN algorithm is very efficient and accurate in predicting lymph node metastases, which reduces the workload on the radiologist and minimizes differences between different diagnostic levels. Some other representative research about lymph node metastasis are listed in Table 2 [52][53][54][55]57,58,72].…”
Section: Radiological Diagnosismentioning
confidence: 99%